Current implementation of the circular economy in enterprises in the Czech Republic - Otakar Ungerman; Jaroslava Dědková (Review of Economic Perspectives, 2021)
The subject of this paper is the contemporary use of the circular economy in business practice. The topicality of this theme was the reason for resolving the main objectives, which were to determine how enterprises in the Czech Republic are currently involved in the circular economy. The authors focused on empirical research, the methodological framework of which contains three interrelated parts. The basis was secondary research from scientific databases, which was followed up by the primary research. The objects of the primary research were based on three research questions, which were focused on the use of standardised environmental activities, the identification of tools of the circular economy and determining their importance. The research was evaluated using the methods of content analysis, descriptive and inductive statistics. The research showed that 71 % of enterprises present themselves as taking an active approach to the environment beyond the scope of the statutory obligations. Enterprises then make most use of regulatory tools such as the ISO 14001 standard or Ecodesign. An in-depth interview was used to identify sixteen tools of the circular economy as they are perceived by enterprises. When assessing importance, the highest rated tool was reducing energy consumption in production, waste from production, the consumption of materials, emissions and minimization of waste. Statistically significant differences were also identified with these tools. The research showed that the circular economy is most used in automotive industry enterprise.
Keywords: L10; L19; M11; M14; Q56; Q57; 330; circular economy; environmental policy; recycling; corporate social responsibility